THU0361 Prescription patterns of biological disease modifying drugs and biosimilars in ankylosing spondylitis – a collaboration between biological registers in the five nordic countries. (15th June 2017) - Glintborg, B; Chatzidionysiou, K; Askling, J; Aaltonen, K; Kristianslund, E; Gudbjornsson, B; Nordström, D; Hetland, ML; Dreyer, L; Kristensen, LE; Jørgensen, TS; Eklund, K; et al.
Abstract : Background: Large-scale real life observational cohorts are needed to study effectiveness and early signals of rare safety issues of new biological disease modifying drugs (bDMARDs) and biosimilars (bsDMARDs) in ankylosing spondylitis (AS). Combining data from biological registries would facilitate this. The Nordic countries have several similarities that would justify such aggregated analyses including similar health care systems with universal access to population based health care, availability of b/bsDMARDs through a tax-paid system and the registration of use and effectiveness of bDMARDs in inflammatory diseases in a prospective manner in drug registries. Objectives: To explore the prescription patterns of old (TNF-inhibitors) and newer bDMARDs (secukinumab, ustekinumab) including bsDMARDs (SB4, CT-P13) over time in AS in the Nordic countries in order to illustrate the potential of a common Nordic collaboration. Methods: Data regarding the numbers of AS patients (pts) (ICD10 code M45) who initiated bDMARD treatment (irrespective of treatment course number) during the period 2011–2016 were collected from the Nordic rheumatologic biological registries SRQ (Sweden), NOR-DMARD (6 Norwegian treatment centres), DANBIO (Denmark), ROB-FIN (Finland, 2011–2015) and ICEBIO (Iceland). Results: In total, 6, 610 bDMARD treatment initiations were identified (Sweden 3654, Norway 1078, Denmark 782, Finland 789, Iceland 307). The prescription patterns of bDMARDs changed substantially over time. In 2016, the number of pts initiating a bsDMARDs exceeded those starting an originator bDMARD (figure). Few patients were treated with ustekinumab (Denmark <10 pts, Finland <10, Sweden 26) and secukinumab (Denmark <10 pts, Sweden 57). Conclusions: The use of bsDMARDs in AS is rapidly increasing. The use of drugs with new modes of action is still low, which illustrates the need for collaboration across countries to provide real life data with sufficient power for new innovative therapies in the future. The Nordic rheumatologic registries represent a unique opportunity to study effectiveness and safety of bDMARDs, including bsDMARDs in AS. Acknowledgements: Partly funded by a grant from NordForsk Disclosure of Interest: B. Glintborg Grant/research support from: abbvie, K. Chatzidionysiou: None declared, J. Askling Grant/research support from: AbbVie, Eli Lilly, Janssen, Merck, Pfizer, Roche, UCB, Samsung, K. Aaltonen Speakers bureau: AbbVie, BMS, Janssen, MSD, Pfizer, Roche, UCB, E. Kristianslund: None declared, B. Gudbjornsson Grant/research support from: Actavis, Celgene, MSD, Pfizer, D. Nordström Speakers bureau: AbbVie, BMS, Lilly, MSD, Novartis, Pfizer, Roche, UCB, M. Hetland Grant/research support from: Orion, BMS, AbbVie, Biogen, Pfizer, MSD, L. Dreyer Speakers bureau: MSD, UCB, Janssen Pharmaceuticals, L. E. Kristensen Speakers bureau: Pfizer, AbbVie, Biogen, Amgen, UCB, Celegene, BMS, MSD, Novartis, Eli Lilly, Janssen pharmaceuticals, T. Jørgensen Speakers bureau: AbbVie, Roche, Novartis, UCB, Biogen, K. Eklund: None declared, G. Grondal: None declared, S. Ernestam: None declared, J. Joensuu Grant/research support from: Pfizer, T. Kvien Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, UCB, E. Lie Speakers bureau: AbbVie, Celgene, Hospira, Pfizer, K. Fagerli: None declared, A. J. Geirsson: None declared, H. Jonsson: None declared, L. Jacobsson Consultant for: Abbvie, Celegen, MSD, Novartis, UCB